Institutionalization of the development management system in Poland = Instytucjonalizacja systemu zarządzania rozwojem w Polsce - Sługocki, Waldemar (Zielona Góra: Faculty of Economics and Management Press)
The Polish development policy was shaped along with the process of political transformation and integration with the European Union. After 1990, the management of development policy had a provisional character, in fact the system did not exist. At the national level, there was certain lack of the legal financing. The progressively progressing process of European integration, the transfer of pre-accession funds and the prospect of EU membership and also the possibility of implementing cohesion policy have enabled the adoption of solutions appropriate for many EU Member States.
Keywords: rozwój kraju; system; zarządzanie; system zarządzania rozwojem; transformacja; polityka publiczna; development; management; development management system; transformation; public policy